2006
DOI: 10.1002/per.574
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent personality, problem behaviour and the quality of the parent–adolescent relationship

Abstract: The relationship between adolescent personality and problem behaviour has been well established. However, relatively little attention has been given to the role of the social environment in the association between adolescent personality and problem behaviour. We tested the mediating and moderating role of the quality of the parent-adolescent relationship in the associations between adolescents' personality traits and problem behaviour. The sample consisted of 140 adolescents (11 to 18 years of age) and both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 35 publications
3
39
1
Order By: Relevance
“…On the other hand, youth with high conscientiousness scores who have authoritative parents are at low risk for deviance (Prinzie et al, 2010). Relevant to this last point, Manders et al (2006) concluded that the quality of parentchildren relations mediates the association between personality characteristics (agreeableness, emotional stability, and conscientiousness) and externalizing behaviors.…”
Section: Personality and Deviancementioning
confidence: 94%
See 4 more Smart Citations
“…On the other hand, youth with high conscientiousness scores who have authoritative parents are at low risk for deviance (Prinzie et al, 2010). Relevant to this last point, Manders et al (2006) concluded that the quality of parentchildren relations mediates the association between personality characteristics (agreeableness, emotional stability, and conscientiousness) and externalizing behaviors.…”
Section: Personality and Deviancementioning
confidence: 94%
“…De Clercq, Van Leeuwen, De Fruyt, Van Hiel, and Mervielde (2008) found significant interactions between low agreeableness, emotional stability, and negative paternal control. Manders et al (2006) found that adolescents with low scores on emotional stability and conscientiousness and who had poor relations with their parents were at greater risk for externalized behaviors.…”
Section: Personality and Deviancementioning
confidence: 98%
See 3 more Smart Citations